Large dielectric switch effects induced by an order–disorder transformation in cyclopropylamine perchlorate crystals. Issue 3 (22nd December 2021) - Gao, Zhangran; Wu, Yuying; Jiao, Shulin; Tang, Zheng; Sun, Xiaofan; Li, Dong; Cai, Hong-Ling; Wu, X. S.
Abstract : A large dielectric switch effect up to 10 3 caused by an order–disorder structural phase transition is found in cyclopropylamine perchlorate (CPA-ClO4 ) crystals at around 230 K ( T c ) and 220 K ( T ′c ). Abstract : Solid-state crystals with two distinct dielectric states can be a physical practice in binary-based technologies. A large dielectric switch effect up to 10 3 caused by an order–disorder structural phase transition is found in cyclopropylamine perchlorate (CPA-ClO4 ) crystals at temperatures around 230 K ( T c ) and 220 K ( T ′c ). Large dielectric switch effects here can be compared to that of the famous ceramic oxide dielectrics. As far as we know, this is the highest dielectric switch effect in simple organic salt crystals and organic–metal compounds so far. If the phase transition temperature can be adjusted by molecular manipulation, one of the most promising candidates for technological applications may emerge in the future.